An iterative Bregman regularization method for optimal control problems with inequality constraints. (1st December 2016) - Pörner, Frank; Wachsmuth, Daniel
Abstract : We study an iterative regularization method of optimal control problems with control constraints. The regularization method is based on generalized Bregman distances. We provide convergence results under a combination of a source condition and a regularity condition on the active sets. We do not assume attainability of the desired state. Furthermore, a priori regularization error estimates are obtained.